2018
DOI: 10.3390/en11051131
|View full text |Cite
|
Sign up to set email alerts
|

The Influences of Various Testing Conditions on the Evaluation of Household Biomass Pellet Fuel Combustion

Abstract: Direct combustion of solid biomass fuel is one of the most common energy sources in developing countries. Evaluation of technology for household biomass pellet fuel combustion is critical, since promoting poorly designed devices may have risks due to exposure to high levels of emissions. This study evaluated the effects of various testing conditions on a top-lit forced-up-draft semi-gasifier cooking stove. An orthogonal test was designed with different fuel masses, chamber heights, air supply rates, and ending… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…In the case of pellets modified with lime from the second research period, ash generation amounted to 1.91-9.71% (average of 2.98% ± 0.95%), and the calorific value was 16.32-20.70 MJ·kg −1 (average of 18.83 ± 0.78 MJ·kg −1 ). The calorific values obtained were similar to those reported by other authors for pellets made from wood mass [33][34][35]. Some authors reported a higher calorific value for wood pellets of 20.3-20.8 MJ·kg −1 , with significantly lower ash generation of 0.27-0.39%.…”
Section: Biomass Propertiessupporting
confidence: 88%
See 1 more Smart Citation
“…In the case of pellets modified with lime from the second research period, ash generation amounted to 1.91-9.71% (average of 2.98% ± 0.95%), and the calorific value was 16.32-20.70 MJ·kg −1 (average of 18.83 ± 0.78 MJ·kg −1 ). The calorific values obtained were similar to those reported by other authors for pellets made from wood mass [33][34][35]. Some authors reported a higher calorific value for wood pellets of 20.3-20.8 MJ·kg −1 , with significantly lower ash generation of 0.27-0.39%.…”
Section: Biomass Propertiessupporting
confidence: 88%
“…Emissions of pollutants into the atmosphere strongly depend on both the type of biomass used as fuel and the combustion conditions [6,17]. Zhang et al [34] noted highly varied CO emissions in a wide range of 43-201 g·kg −1 for pellets under different combustion conditions. In the context of the results of this study, this particular element seems to be important.…”
Section: Analysis Of the Combustion Process For Emissionsmentioning
confidence: 99%
“…Straws are produced in farmlands. Based on the principle of rural energy utilization, straws and biomass pellet can be used for heating and cooking by farmers [75,76]. Compared with small-size straw formed particles, the bundled straws can be used for heat supply in rural areas at low costs (1.53-2.05 $•m −2 ) [53].…”
Section: Characteristics Of Straw Blocks For Fuelmentioning
confidence: 99%
“…The ending points did not have significant effects on thermal efficiency and the carbon dioxide emission factor but did affect particulate matter emission. A relatively lower chamber height demonstrated a better performance on thermal metrics [17].…”
Section: Introductionmentioning
confidence: 95%
“…Aziz et al developed an innovative study using a fluidized bed dryer with superheated steam and its integration into a gasification-combined cycle system power generation [16]. Zhang et al evaluated the effects of various testing conditions on a top-lit forced-up-draft semi-gasifier cooking stove [17]. The investigation showed that using forced secondary air and more fuel tended to improve both thermal and gas emission performances.…”
Section: Introductionmentioning
confidence: 99%